As ações coletivas na tutela do direito ao meio ambiente e à saúde - Campos, Juliana Rose Ishikawa da Silva (2015)
This dissertation presents a discussion on how the legal system can protect transindividual rights, particularly the right to health and environment. Those rights have been chosen for their importance in the current risk society. For that matter the 1988 Federal Constitution, various laws, legal doctrine, case law and some documents on the subject were examined (using the bibliographical and documentary methods). The discussion about the research results and reflections on the topic begins with a historical and philosophical analysis on the “evolution” of fundamental rights, going through the rights to freedom (liberal model), through the social rights (Welfare State) and reaching the solidarity rights (characteristic of the constitutional state and democratic state). At the second chapter was analyzed the rights to health and environment (concepts, principles, jurisprudence, etc.), forging a relationship between them. The foundation of this relationship was sought by analyzing the principles common to both, the environmental damage (which can also affect health) and especially the joint actions that have been developed or proposed – Environmental Health Surveillance and “National Policy of Environmental Health”. Despite the importance of these actions which are primarily preventive (and precautionary), it is clear that such rights have been threatened and violated in various ways. Hence the need of jurisdictional instruments for their protection. In a doctrinal and jurisprudential analysis it was found that the collective action were more effective and comprehensive – justifying them to be the subject of the third chapter. This chapter began with an approach to the evolution of the collective process in Brazil. The collective process microsystem, which includes the popular action, the civil action and the collective writ, among other non-judicial instruments was critically analyzed. Said microsystem standard is the paradigm from the Consumer Code, which among other contributions brought the concepts of diffuse rights, collective rights and individual homogeneous rights. Still in the third chapter the main and most emblematic institutions of the collective rights were analyzed – distribution of the charge of proof, expertise, res judicata and settlement. It was presented some problems and proposals to encode the collective process and its deal with those institutes. Finally, three actions were analyzed, focusing on the question of legitimacy and other problems brought on by legislation and case law. All this was done to demonstrate de importance of these actions in the protection of environment and health, among others transindividual rights and intention to cooperate with the legal debate on the protection of fundamental rights, especially the collective rights which are difficult to treat.